Endowment Buildings in the Bosnian Sanjak: The 1560’s - Čar-Drnda, Hatidža (Prilozi za orijentalnu filologiju, 2017)
This paper presents endowments /waqfs/ in the Bosnian sanjak until the end of the seventh decade of the sixteenth century. The work is based on the Register of the Bosnian Sanjak from 1565 and the literature on endowment buildings from the period not covered by this Register. The paper presents the follovving buildings: mosques and masjids, zavias, madrasahs, public baths, soup kitchens, hostels, caravansarais, roofed markets and bridges. Although the paper does not include ali the buildings endowed in the said period, we can see what impact endorvments had on the develop- ment of cities and towns in Bosnia and Herzegovina.